Feasibility of New Method for the Prediction of Clinical Trial Results Using Compressive Sensing of Artificial Intelligence - Miyagi, Yasunari; Keiichi Fujiwara; Hisanaga Nomura; Koji Yamamoto; Robert L Coleman (British Journal of Healthcare and Medical Research, 2023)
To develop a new method for interim analysis to obtain the p-values distribution profile of the log-rank test and the statistical power at various information fraction by iteratively predicting the lacking time data of censored and uncensored cases respectively for each arm at the time when the determined sample size will be achieved. A compressive sensing algorithm derived from artificial intelligence was developed for comparing two groups of clinical trial data from real-world databases of deidentified individual participant-level data. The judgement of the interim analysis was compared to the conventional method, with our method demonstrating that it was at least comparable to the conventional method. The power by our method was higher than the conditional power of the conventional method. When α-error by log-rank test was focused, our method seemed to have made the right decision earlier than the conventional method. It may be possible to expand the options of applicable methods for interim analysis. It would be helpful in establishing efficacy and futility judgement in clinical trials.